Frontispiece: (View 4/2020). Issue 4 (2nd December 2020) - Unknown
Abstract : Zybio Inc. is a high‐tech enterprise specialized in R&D, manufacture, sales and technical services of In Vitro Diagnostic reagents and equipment. The main products cover chemistry, immune‐POCT, molecular diagnosis, hematology, microbial detection and raw materials. Fully Automated Microbial Mass Spectrum Detection System EXS3000 Patented ion repulsion technology, eliminating the interference of impurity ions and improving instrument life. Providing offline stand‐alone database and synchronous online cloud retrieval function, detectable samples cover more than 4000 species of microorganisms. Positive and negative ion dual modes, increasing the range of detectable sample types. Artificial intelligence typing software, which can classify closely related microorganisms and their subspecies, such as Escherichia coli and Shigella .